Political Economy: Success or Failure? - Bruno S. Frey; Lasse Steiner (Contemporary Economics, 2012)
The Political Economy and Public Choice approaches have promoted the study of interactions between the economy and the polity for over 60 years now. The present paper endeavours to provide a critical discussion of this literature and its achievements. In particular, it begins with the different approaches based on empirically tested or politometric models and it then proceeds to discuss different studies of the effects that particular rules of the game have on politico-economic outcomes. The third section of the paper will address studies that take institutions to be endogenous and aims to explain why particular institutions emerge. Finally, the question of whether Political Economy has been a success or a failure will be tackled. While the success in terms of the position it has gained in economic research and teaching is undeniable, a look at one of the most thriving recent areas of economics, happiness research, will reveal that some of its fundamental lessons are all too often disregarded.
Keywords: H10; B25; A11; 330; political economy; public choice; constitutional economics; institutions